Cultural traditions in Canada - Aloian, Molly (New York : Crabtree Publishing, 2014)
Describes the different holidays and traditions in various parts of Canada and the ways in which Canadians celebrate family occasions.
What are cultural traditions? -- Christmas in Canada -- Happy New Year! -- The Quebec winter carnival -- Family Day -- Good Friday and Easter -- Victoria Day -- National Aboriginal Day -- Canada Day -- The Calgary stampede -- Labor day -- Happy Thanksgiving! -- Halloween -- Remembrance Day.
Includes index.
Includes bibliographical references and index.
Age 5-8.
Grade K to 3.
Keywords: Holidays -- Canada -- Juvenile literature; Festivals -- Canada -- Juvenile literature; Holidays -- Canada; Festivals -- Canada; Festivals; Holidays; Manners and customs; Canada -- Social life and customs -- Juvenile literature; Canada -- Social life and customs; Canada; Juvenile works